Project Measurement - Neuendorf, Steve (Berrett-Koehler Publishers, 2001)
Learn how to create a measurement-oriented program for your unique organization. With new insights on measurement as a communications tool, this book offers step-by-step guidance on how to use specific quantitative actions-and-results assessments to ensure the success of key initiatives. You'll master the new skills needed to incorporate stakeholder requirements into the structure and operation of the measurement program. You'll also learn how to implement a measurement program and develop understanding of the measurement life cycle, including how to keep your tactics and processes evolving to stay in step with your organization and new challenges.